1993
DOI: 10.1001/archinte.153.9.1093
|View full text |Cite
|
Sign up to set email alerts
|

Excess body weight. An underrecognized contributor to high blood cholesterol levels in white American men

Abstract: Excess body weight is associated with deleterious changes in the lipoprotein profile. Higher BMI was associated at all ages with higher plasma triglyceride level, lower HDL cholesterol level, and higher total and non-HDL cholesterol levels. In young men, the higher total cholesterol level was reflected mainly in the LDL cholesterol level; in middle-aged and older men, in the non-HDL fraction. Programs to reduce coronary heart disease by improving lipid levels should include more emphasis on achieving and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
118
0
5

Year Published

1993
1993
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 67 publications
16
118
0
5
Order By: Relevance
“…This suggests that obesity counteracts the promotive effects of menopause on IHD. On the other hand, although obesity is not a direct risk factor for IHD, 37,38 it causes elevated blood pressure 39 and hypercholesterolemia 40 and, therefore, can be deemed an indirect coronary risk factor. In view of the complex interactions between obesity and IHD risk factors, no simple conclusion can be reached about whether obesity has a promotive or suppressive effect on IHD in women.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that obesity counteracts the promotive effects of menopause on IHD. On the other hand, although obesity is not a direct risk factor for IHD, 37,38 it causes elevated blood pressure 39 and hypercholesterolemia 40 and, therefore, can be deemed an indirect coronary risk factor. In view of the complex interactions between obesity and IHD risk factors, no simple conclusion can be reached about whether obesity has a promotive or suppressive effect on IHD in women.…”
Section: Discussionmentioning
confidence: 99%
“…High serum lipids commonly accompany the obese state (Eckel, 1999;National Heart, Lung and Blood Institute, NIH, 1998;Denke et al, 1993). The NCEP recommends a step-wise dietary therapy with emphasis on reducing dietary saturated fat and cholesterol with weight loss, if patients are overweight (NCEP, 1993).…”
Section: Lipoprotein Response To Weight Loss Hh Ditschuneit Et Almentioning
confidence: 99%
“…The report also addressed the need for improving weight control and physical activity. This new emphasis on weight control is partially credited to the growing body of information demonstrating a causal relationship between reduced body weight and improved serum lipids (National Heart, Lung and Blood Institute, NIH, 1998;Denke et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…8,9,12,38 Several studies have found patterns of fat distribution, particularly abdominal or central obesity, to be more closely related than body weight or BMI to serum risk factors for cardiovascular disease. 39,40 Other studies have concluded that overall obesity is as important as fat distribution, especially for associations with lipidalipoprotein concentrations.…”
Section: Cross-sectional Comparisonsmentioning
confidence: 99%